MASA DEPAN NAMA DI INDONESIA - Dedi Sulaeman; Dhisa Ayu Damayanti; Muhamad Iqbal Al Hilal (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
Name is a designation or label given to objects, people, places, products and even ideas or concepts, which are usually used to distinguish one another. As social beings, humans are given a name as a differentiator between one another. However, in some people in Indonesia there is a custom to call the name of the Hajj as a tribute to people who have performed the pilgrimage. Habits like this of course will have an impact on the same nickname for people who already have the title of Hajj. Not a few for a community that has already had the pilgrimage called Hajj which of course confuses the person because several people are called by the same name. So what if one day everyone in Indonesia has a Hajj title. Will everyone in Indonesia be named Haji? This article discusses the future of the Indonesian name on the basis that it is part of the Indonesian people's habit of using informal, binding and declining names. This article is prepared based on adequate literature study. By using the meta-analysis method, the writer analyzes and interprets the existing data and supports each other.